A 2-Level Iterated Tabu Search Algorithm for the Quadratic Assignment Problem - Misevičius, Alfonsas; Kuznecovaitė (Verenė), Dovilė (Information & Media, 2019)
In this paper, a 2-level iterated tabu search (ITS) algorithm for the solution of the quadratic assignment problem (QAP) is considered. The novelty of the proposed ITS algorithm is that the solution mutation procedures are incorporated within the algorithm, which enable to diversify the search process and eliminate the search stagnation, thus increasing the algorithm’s efficiency. In the computational experiments, the algorithm is examined with various implemented variants of the mutation procedures using the QAP test (sample) instances from the library of the QAP instances – QAPLIB. The results of these experiments demonstrate how the different mutation procedures affect and possibly improve the overall performance of the ITS algorithm.
Keywords: computational intelligence; combinatorial optimization; heuristic algorithms; tabu search; mutation procedures; quadratic assignment problem